Penciptaan Film Pendek Bertemakan Dampak Dari Keluarga Disfungsi Terhadap Kesehatan Mental Anak - Bachrul Restu Bagja; Resthu Firthian; Agus Darmawan; Rubi Al Firdaus (Universitas Multimedia Nusantara, 2022)
Family is the first environment for children to learn and shape character in the future. A successful family is seen from the achievement of welfare for all its members and can manage their family well, providing a sense of security, comfort and mutual respect. Meanwhile, family dysfunction is a condition that interferes with the functioning of a family. Healthy families quickly return to normal functioning after experiencing problems, while dysfunctional families tend to become chronic so that children do not get the needs they should. The children at the Nurun Nisa Cicurug Sukabumi Orphanage Foundation, based on data in 2020, mostly experienced dysfunctional family problems due to lack of education on the role of parents in children's mental health in the family environment. The campaign using short films was carried out as an effort to raise awareness of the importance of the role of parents for children's mental health. The target audience in this study is aimed at teenagers aged 17-25 years who want to marry young in order to get education about the things that cause dysfunctional families. The use of descriptive qualitative methods and analysis based on literature studies aims to obtain a factual, accurate and systematic picture based on various facts in dysfunctional family problems. The short film is based on a true story that is reprocessed into a unified narrative element. Behavior that is carried out by dysfunctional families is considered normal behavior, in fact it can disrupt the mental health of children. Keywords: family; dysfunction; mental health; campaign; short film.